Characterization of an Antiviral Component in Human Seminal Plasma - Chen, Ran; Zhang, Wenjing; Gong, Maolei; Wang, Fei; Wu, Han; Liu, Weihua; Gao, Yunxiao; Liu, Baoxing; Chen, Song; Lu, Wei; Yu, Xiaoqin; Liu, Aijie; et al. (Frontiers in Immunology, 2021)
Numerous types of viruses have been found in human semen, raising concerns about the sexual transmission of these viruses. Although most seminal viruses lose their infectivity, the overall roles of semen in viral infection and transmission have yet to be fully investigated. In the present study, we analyzed the effect of seminal plasma (SP) on viral infection by focusing on the mumps viral (MuV) infection of HeLa cells. MuV efficiently infected HeLa cells in vitro. MuV infection was strongly inhibited by the pre-treatment of viruses with SP. Moreover, SP inhibited MuV infection through the impairment of the virus’s attachment to cells. The antiviral activity of SP was resistant to the treatment of SP with boiling water, Proteinase K, RNase A, and DNase I, suggesting that the antiviral factors are not proteins and nucleic acids. We also showed that the prostatic fluid (PF) was responsible for the inhibition of MuV infection, whereas the epididymal fluid and seminal vesicle extract did not inhibit MuV infection. Using high-performance liquid chromatography, we isolated a < 3 kDa hydrophilic fraction from SP or PF, which had an inhibitory effect on MuV infection. However, this inhibitory effect was not specific to MuV, as the herpes simplex virus 1, dengue virus 2, and adenovirus 5 infections were also inhibited by SP, PF, and the isolated fraction. Our findings suggested that SP contains a prostate-derived antiviral factor that potentially limits the sexual transmission of various viruses.